Hypouricemic Effects of Ganoderma applanatum in Hyperuricemia Mice through OAT1 and GLUT9 - Yong, Tianqiao; Chen, Shaodan; Xie, Yizhen; Chen, Diling; Su, Jiyan; Shuai, Ou; Jiao, Chunwei; Zuo, Dan (Frontiers in Pharmacology, 2018)
Ganoderma applanatum (G. applanatum) dispels wind to eliminate dampness and exhibited nephron- and liver-protective effects as noted in Chinese herbal classic literature; it might also affect hyperuricemia. Therefore, we examined the hypouricemia effects and mechanisms underlying G. applanatum on chemical-induced hyperuricemia in mice. Ethanol (GAE) and water (GAW) extracts were prepared by extracting G. applanatum in ethanol (GAE), followed by bathing the remains in water to yield GAW. GAE and GAW were administered orally at different doses to hyperuricemia mice, while allopurinol and benzbromarone served as positive controls. Both GAE and GAW showed remarkable hypouricemia activities, rendering a substantial decline in the SUA (serum uric acid) level in hyperuricemia control (P<0.01). Moreover, the urine uric acid (UUC) levels were enhanced by GAE and GAW. In contrast to the evident renal toxicity of allopurinol, GAE and GAW did not show a distinct renal toxicity. Almost no suppressing effect was observed on the XOD activities. However, compared to the hyperuricemia control, OAT1 was elevated remarkably in mice drugged with GAE and GAW, while GLUT9 was significantly decreased. Similar to benzbromarone, GAE decreased the URAT1 protein levels significantly (P<0.01), while GAW did not display a similar effect. GAE and GAW downregulated the level of CNT2 proteins in the gastrointestinal tract of hyperuricemia mice. Thus, G. applanatum produced outstanding hypouricemic effects, mediated by on renal OAT1, GLUT9, and URAT1 and gastrointestinal CNT2 expressions that might elevate urine uric secretions and decline in the absorption of purine in the gastrointestinal tracts. G. applanatum showed little negative influence on inner organs. By docking screening, four top-ranked compounds were identified that necessitated further investigation.